The Strength of Proof on Underwrited Deed in Waarmeking by a Notary - Setiawan Widiyoko (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The power of proof of an underhand deed as evidence in court in connection with the authority of a Notary in carrying out Legalization and Waarmeking based on articles 1874, 1874 (a) and 1880 BW of the letter evidence must have legalization or waarmeking from the authorized official. In Decision Number 13 PDT/2020/PT.MTR there is a difference in Judex Factie in the trial between the Praya District Court and the Mataram High Court. This study analyzes how aspects of the strength of proof of underhand deeds that have been legalized or waarmeking by a Notary and legal considerations applied by judges in examining and deciding the case. This study uses a normative juridical legal research method, namely legal research conducted by examining materials derived from various laws and regulations and other materials from various literatures that have correlation and relevance to the problems to be studied, as well as legal theories and opinions of scholars. The underhanded deed which is waarmeking is perfect evidence, the contents of the underhand deed that have been registered at a Notary with the signing of the parties are valid, the proof value of the underhand deed must meet formal and material requirements, then the proof value is the same as the authentic deed, namely the proof value. perfectly attached and binding, while the power of proof of a deed under the hand that has been waarmeking in evidence at trial has imperfect proving power when each party denies the contents of the agreement. Notaries in carrying out their duties must be in accordance with applicable laws and regulations so that there are no disputes over agreements that have been waarmeking. so that it has perfect proof of certainty in the eyes of the law.